The determinants of tax e-filing among tax preparers in Malaysia - Abdul Aziz, Saliza (World Business Institute, Australia, 2012)
The evolutions of tax filing system had gone through a tremendous change.The transformation of manual to electronic shows the successful of self-assessment system implementation.Undeniably, the progression had consumes a huge amount of expenditures in ensuring the infrastructure and facilities capable to accommodate the technology. In spite of the easiness and efficiency of e filing, the acceptability of users on using such facility remains unsatisfactorily.Why sour? What went wrong? And how could the government improve such situation? These are the key questions that need to be addressed.At the moment, a comprehensive explanation to address the above problem still remains inconclusive.Thus, this conceptual paper tries to identify and close some of the gaps that are not addressed by the literature.The main objective of this study is to gain understanding on the gaps existed in the e-filing among the tax preparer. In seeking for the imperative answers, this research is design for the following objectives (1) to determine the level of acceptance of tax e-filing among Malaysian tax preparers; (2) to identify the determinants of tax e-filing acceptability; and (3) to examine how the factors identified in two (2) are related to tax e-filing acceptability.